Animal‐cell culture media: History, characteristics, and current issues. (21st March 2017) - Yao, Tatsuma; Asayama, Yuta
Abstract: Background: Cell culture technology has spread prolifically within a century, a variety of culture media has been designed. This review goes through the history, characteristics and current issues of animal‐cell culture media. Methods: A literature search was performed on PubMed and Google Scholar between 1880 and May 2016 using appropriate keywords. Results: At the dawn of cell culture technology, the major components of media were naturally derived products such as serum. The field then gradually shifted to the use of chemical‐based synthetic media because naturally derived ingredients have their disadvantages such as large batch‐to‐batch variation. Today, industrially important cells can be cultured in synthetic media. Nevertheless, the combinations and concentrations of the components in these media remain to be optimized. In addition, serum‐containing media are still in general use in the field of basic research. In the fields of assisted reproductive technologies and regenerative medicine, some of the medium components are naturally derived in nearly all instances. Conclusions: Further improvements of culture media are desirable, which will certainly contribute to a reduction in the experimental variation, enhance productivity among biopharmaceuticals, improve treatment outcomes of assisted reproductive technologies, and facilitate implementation and popularization of regenerative medicine.